Correction: Generalized Langevin dynamics: construction and numerical integration of non-Markovian particle-based models. Issue 48 (30th November 2018) - Jung, Gerhard; Hanke, Martin; Schmid, Friederike
Abstract : Correction for 'Generalized Langevin dynamics: construction and numerical integration of non-Markovian particle-based models' by Gerhard Jung et al., Soft Matter, 2018, DOI: ;10.1039/c8sm01817k .